THE EFFECT OF DISCOVERY-INQUIRY LEARNING MODELS APPLICATION TOWARD LEARNING ACHIEVEMENT ON COLLOID SUBJECT MATTER REVIEWED FROM STUDENTS INITIAL ABILITY - Louisiana Muliawati; Wildan Wildan; Agus Abhi Purwoko (IKIP Mataram, 2013)
The research has been done to evaluate the influence of discovery-inquiry learning model application on colloid subject to students learning result refer to their initial ability in SMAN 7 Mataram academic year 2012/2013. The result of this research is to know: (1) The result of chemistry learning of students who have high initial ability and low initial ability that learn through discovery-inquiry model with students who follow expository learning in SMAN 7 Mataram. (2) Interaction between learning model and student's early ability to student's chemistry learning result in SMAN 7 Mataram. Research Data processing was conducted through Microsoft Excell. The results of the data analysis showed that students learning results taught using the discovery-inquiry model were higher than using expository in both students with high initial ability and low initial ability. There is no interaction between model and initial ability with students learning result.